Three Cases of Bartonella Quintana Infection in Children. Issue 5 (May 2015) - Magnolato, Andrea; Pederiva, Federica; Spagnut, Giulia; Maschio, Massimo; Ventura, Alessandro; Taddio, Andrea
<x xml:space="preserve">Abstract</x> We present 3 children affected by B. quintana infection treated at the IRCCS Burlo Garofolo of Trieste between March and April 2013. B. quintana infection is rare but it should be suspected in patients with fever and lymphadenopathy who do not respond to conventional antibiotic treatment. All patients had a complete recovery without sequelae or relapses.